On the possibility of internal conflict on Crete between the Proto- and Neopalatial period. The Pax Minoica re-examined: _________________________________ - Borowka, Dawid (Acta Archaeologica Lodziensia, 2019)
The Pax Minoica (Minoan Peace), a concept formulated by Sir Arthur Evans was, and still is, one of the most preeminent paradigms on Minoan culture. According to this theory Crete was protected from threats by a strong and far-reaching fleet. It was referred to in the works of Herodotus and Thucydides, who wrote about King Minos conquering the sea and triumphing over pirates. This state of affairs was supposed to explain the lack of fortifications in Crete during the Bronze Age and the relative peace prevailing on the island itself. Since the time Evans carried out his research, numerous examples of defensive architecture have been found on the island, as well as weapons used by the Minoans. They shed new light on our knowledge of the various stages of the development of Minoan civilization. In this article an attempt will be made to take closer look at them between EM II and MM III periods. This will allow us to verify if the alleged internal peace existed on Crete during the Bronze Age. REFERENCES Alexiou, S. 1979. Τειχη και ακροπολεις στη μινωικη Κρητη. Kretologia 8, 41-56. Alusik, T. 2007. Defensive Architecture of Prehistoric Crete, Oxford. Amato, R.D’ & Salimbeti A. 2013. Early Aegean Warrior 5000-1450 BC, Osprey Publishing. Betancourt, P.P., Davaras, C., Dierckx H.M.C., Ferrence S.C., Hickman J., Karkanas P., McGeorge, P.J.P., Muhly, J., Reese, D.S., Stavropodi, E., Langford-Verstegen L., Chlouveraki, S. 2008. Excavations in the Hagios Charalambos cave. Hesperia: The Journal of the American School of Classical Studies at Athens 77(4), 539-605. Brabander, S. 2012. Defensible or not defensible? Guard houses from Middle and Late Minoan Crete revisited, using GIS and Space Syntax, Leiden. Branigan, K. 1974. Aegean Metalwork of the Early and Middle Bronze Age, Oxford. Branigan, K, 1967. A Transitional Phase in Minoan Metallurgy. Annual of the British School at Athens 62, 183-203. Branigan, K, 1968. Copper and Bronze Working in Early Bronze Crete, Lund. Branigan, K, 1967. The Early Bronze Age Daggers of Crete. Annual of the British School at Athens, 211-239. Branigan, K, 1999. The Nature of Warfare in the Southern Aegean During the Third Millenium B.C.. In Polemos: le contexte guerrier en Egée à l’âge du Bronze: actes de la 7e Rencontre égéenne internationale, Université de Liège,14-17 avril 1998, 87-94. Castelden, R. 1990. Minoans, London. Colburn, C.S. 2008. Exotica and the Early Minoan Elite: Eastern Imports in Prepalatial Crete. American Journal of Archeology, 112(2), 203-224. Dickinson, O. 1999. Robert Drew’s theories about the nature of warfare in the late Bronze Age. In Polemos: le contexte guerrier en Egée à l’âge du Bronze: actes de la 7e Rencontre égéenne internationale, Université de Liège, 14-17 avril 1998, 21-29. Driessen, J., Macdonald, C. 1984. Some Military Aspects of the Aegean in the Late Fifteenth and Early Fourteenth Centuries B.C.. Annual of the British School at Athens 79, 49-74. Driessen, J. 1997. Observations on the Modification of the Access Systems of Minoan Palaces. Aegean Archeology 2, 84-87. Driessen, J. 1999. The Archaeology of Aegean Warfare. In Polemos: le contexte guerrier en Egée à l’âge du Bronze: actes de la 7e Rencontre égéenne internationale, Université de Liège, 14-17 avril 1998, 11-20. Driessen, J. 2002. Towards an archeology of crisis: defining the long-term impact of the Bronze Age Santorini eruption. In Natural disasters and cultural change, London, 251-252. Driessen, C.F. Mcdonald. 1997. The Troubled Island: Minoan Crete before and after the Santorini Eruption. Aegaeum 17. Driessen, J.A MacGillivray. 2011. Swept away in LM IA? Explaining debris position in coastal Neopalatial Crete. In Proceedings of the 10th International Cretological Congress, 99-111. Evans, A.J. 1906. The prehistoric tombs of Knossos. Archaeologia 59, 391-562. Evans, A.J. 1921. Palace of Minos I, London. Evans, A.J. 1928a. Palace of Minos II.1, London. Evans, A.J. 1928b. Palace of Minos II.2, London. Evans, A.J. 1930. Palace of Minos III, London. Evans, A.J. 1935a. Palace of Minos IV.1, London. Evans, A.J. 1935b. Palace of Minos IV.2, London. Evans, A.J. Myres, J.L. 1895. A Mycenaean Military Road in Crete. The Academy 1204. Fitton, L. 2002. Minoans (Peoples of the Past), London, British Museum Press. Floyd, C. 1999. Observations on a Minoan Dagger from Chrysokamino. In Polemos: le contexte guerrier en Egée à l’âge du Bronze: actes de la 7e Rencontre égéenne internationale, Université de Liège, 14-17 avril 1998, 433-442. Frezer, J.G. 1921. Apollodorus, The Library Books 1-3.9, London. Gates, C. 1999. Why are there no scenes of warfare in Minoan art? In Polemos: le contexte guerrier en Egée à l’âge du Bronze: actes de la 7e Rencontre égéenne internationale, Université de Liège, 14-17 avril 1998, 277-283. Godley, A.D. 1920. Herodotus, Histories III, Harvard University Press. Gonen, R. 1975. Weapons of the Ancient World, London. Harding, A. 2004. Warfare: A Defining Characteristic of Bronze Age Europe? In Ancient Warfare: Archaeological Perspectives, Gloucestershire, 157-173. Haysom, M. 2010. The double-axe: A contextual approach to the understanding of a Cretan symbol of the Neopalatial period. Oxford Journal of Archaeology 29.I, 35-55. Hiller, S. 1984. Pax Minoica versus Minoan Thalassocracy. In R. Hägg, N. Marinatos (eds.), Military Aspects of Minoan Culture, The Minoan Thalassocracy: Myth and Reality: Proceedings of the 3rd International Symposium at the Swedish Institiute in Athens 31 May-5 June 1982, 17-31. Hitchcock, L.A. 2000. Minoan Architecture: A Contextual Analysis. Studies in Mediterranean Archeology and Literature Pocket-Book 155. Hockmann, O. 1980. Lanze und Speer im spatminoischen und mykenischen Griechenland. Jahrbuch des Römisch-Germanischen Zentralmuseums Mainz 27, 13-159. Hood, S. 1965. Minoan Sites in the Far West of Crete. Annual of the British School at Athens 60, 99-113. Hood, S. 1980. Shaft Graves Swords: Mycenean or Minoan. In Proceedings of the 4th Cretological Congress, Athens. Hooder, I. 1993. The Narrative and Rhetoric of Material Culture Sequences. World Archeology 25, 268-269. Howard, D. 2011. Bronze Age Military Equipment, Croydon. Ivanova, M. 2007. Things Unfound: Patterns of Warfare in the Early Bronze Age Aegean and Thrace. In I. Galanaki, H. Tomas, Y. Galanakis, R. Laffineur (eds.) Between the Aegean and the Baltic Seas, Prehistory across Borders. Aegaeum 27, 249-256. Kanta, A & Stampolidis, N.C. 2001. Orn ‘ΑΙΠΥ’ in the context of the Defensive Settlements of the End of the Bronze Age, Defensive Settlements of the Aegean and the Eastern Mediterranean after c. 1200 B.C., Nicosia, 95-113. Kilian-Dirlmeier, I. 1993, Die Schwerter in Griechenland (Ausserhalb der Peloponnes), Bulgarien und Albanien (Prahistorische Bronzefunde IV.5), Stuttgart. Knappett, C. 1999. Assesing a Polity in Protopalatial Crete: The Malia-Lasithi. American Journal of Archaeology 103, 615-639. Kopcke, G. 1999. Male Iconography on some Late Minoan Signets. In Polemos: le contexte guerrier en Egée à l’âge du Bronze: actes de la 7e Rencontre égéenne internationale, Université de Liège, 14-17 avril 1998, 342. Kristiansen, K. Larsson, T.B. 2006. The Rise of Bronze Age Society: Travels, Transmissions and Transformations, Cambridge University Press. Krzyszkowska, O. 2005. Aegean Seals: An Introduction, London. Krzyszkowska, O. & Nixon, L. (ed.) 1983. Minoan Society: proceedings of the Cambridge Colloquium, Bristol. Laffineur, R. (ed.), 1999. Polemos: le contexte guerrier en Egée à l’âge du Bronze: actes de la 7e Rencontre égéenne internationale, Université de Liège, 14-17 avril 1998, Aegeaum 19, Liege. Logue, W. 2004. Set in Stone: The Role of Relief carved Stone Vesells in Neopalatial Minoan elite propaganda. Annual of the British School at Athens 99, 149-172. Mannig, S.W. 2008. Formation of the Palaces. The Cambridge Companion to the Aegean Bronze Age, Cambridge, 105-120. Marinatos, N. 1986. Minoan Sacrificial Ritual: Cult Practice and Symbolism (Acta Instituti Atheniensis Regni Sueciae), Stockholm. Marinatos, N. 2010. Minoan Kingship and The Solar Goddess: A Near Eastern Koine, University of Illinois Press. Marinatos, N. 2015. Sir Arthur Evans and Minoan Crete: Creating the Vision of Knossos, I.B. Tauris. Mathieu, J. R. & D.A Meyer, D.A. 2002. Reconceptualising experimental archaeology: Assessing the process of experimentation. Experimental Archaeology, 73-83. McCreery, A.M. 2010. Evidence for Warfare on Crete During the Early and Middle Bronze Age. Temple University (Unpublished MA Thesis). McEnroe, J.C. 2010. Architecture of Minoan Crete, University of Texas Press. Molloy, B. 2007. What’s the Bloody Point: Swordmanship in Bronze Age Ireland and Britain. In The Cutting Edge: Studies in Ancient and Medieval Combat, Stroud, 90-111. Molloy, B. 2010. Swords and Swordsmanship in the Aegean Bronze Age. American Journal of Archaeology 114(3), 406. Molloy, B. 2012. Martial Minoans? War As Social Process, Practice and Event in Bronze Age Crete. Annual of the British School at Athens 107, 87-142. Morgan, L. 1988. The Miniature Wall Paintings from Thera: A Study in Aegean Culture and Iconography, Cambridge. Nowicki, K. 2000. Defensible Sites in Crete.1200-800 BC (LM IIIB/IIIC through Early Geometric). Aegaeum 21. Nowicki, K. 1988. Topography of Refuge Settlement in Crete, Jahrbuch des Römisch-Germanischen Zentralmuseums Mainz 34, 213-234. Nowicki, K. 1988. Investigations in the Cretan Mountains. Archeologia 39, 189-198. Nowicki, K. 1990. The West Siteia Mountains at the turn of the Bronze and Iron Ages. Aegaeum 6, 189-198. Nowicki, K. 1992a. Report on Investigations in Greece. VII. Studies in 1990. Archeologia 42, 137-145. Nowicki, K. 1992b. Report on Investigations in Greece. VIII. Studies in 1991. Archeologia 43, 113-119. Nowicki, K. 1993. Report on Investigations in Greece. IX. Studies in 1992. Archeologia 44, 95-101. Nowicki, K. 1994. A Dark Refuge Centre Near Pefki, East Crete. Journal of the British School at Athens 89, 235- 268. Nowicki, K. 1996. Arvi Fortetsa and Loutraki Kandilioro: Two Refuge Settlements in Crete. Journal of the British School at Athens 91, 253-285. Nowicki, K. 1999. Final Neolithic Refugees or Early Bronze Age Newcomers? The Problem of Defensible Sites in Crete in the Late Fourth Millenium B.C. In MELETEMATA: Studies in Aegean Archaeology Presented to Malcolm H. Wiener as He Enters His 65th Year, vol. II, Aegaeum 20, 575-581. Pashley, R. 1837. Travels in Crete, Cambridge. Peatfield, A. 2008. Minoan and Mycenean Warfare. In The Ancient World at War. A Global History, 87-88. Peatfield, A. 1999. The Paradox of Violence: Weaponry and Martial Art in Minoan Crete. In Polemos: le contexte guerrier en Egée à l’âge du Bronze: actes de la 7e Rencontre égéenne internationale, Université de Liège, 14-17 avril 1998, 67-74. Pendelbury, J.D.S. 1937. Lasithi in Ancient Times. Annual of the British School at Athens 37. Pendelbury, J.D.S. 1933. A Handbook to the Palace of Minos, Knossos 6th edition (1969), London. Piotrowicz, L. 2003. Arystoteles – Polityka, Dzieła wszystkie, t. I, Warszawa. Platon, N. 1971. Zakros. The Discovery of a Lost Palace of Ancient Crete, New York. Renfrew, C. 1982. Polity and Power: Interaction, Intensification and Exploitation. An Island Polity. The Archaeology of Exploitation in Melos, Cambridge. Rutkowski, B. 1991. Petsophas. A Cretan Peak Santuary, Warsaw. Schlager, N. 1997. Minoische bis Rezente Ruinen im fernen Osten Kretas. Dokumentation 1996. Jahreshefte Des Österreichischen Archäologischen Institutes In Wien 66, 1-83. Sakellariou, A. 1975. La scene du ‘siege’ sur le rhyton d’argent de Mycenes d’apres une nouvelle reconstitution. Revue Archeologique, 195-208. Sakellarakis, Y., Sapouna-Sakellaraki, E. 1981. Drama of Death in a Minoan Temple, National Geographic I 59.2, 204-223. Sandars, N. 1961. The First Aegean Swords and their Ancestry. American Journal of Archaeology 65(1), 17-29. Sandars, N. 1963. Later Aegean Bronze Swords. American Journal of Archaeology 64(2), 117-153. Saunders, N. 2012. Beyond the Dead Horizon: Studies in Modern Conflict Archaeology, Oxford. Schoep, I. 2002. The State of the Minoan Palaces or the Minoan Palace-State? Aegaeum 23, 15-22. Shaw, J.W. 2015. Elite Minoan Architecture: Its Development in Knossos, Phaistos and Malia, Philadelphia. Siemieński, L. 1992. Homer- Odyseja, przeł. Lucjan Siemieński, Wrocław. Smith, C.F. 1919. Thucydides: History of the Peloponnesian War I.4, The Loeb Classical Library. Timm, T. 2004. Der Diskos von Phaistos Anmerkungen zur Deutung und Textstruktur. In Indogermannische Forschungen 109, 2004, 204-241. Tsipopoulou M. 1999. Before, During, After: The Architectural Phases of the Palatial Building at Petras, Siteia. In MELETEMATA: Studies in Aegean Archaeology presented to Malcolm H. Wiener as He Enters his 65th Year, vol. II, Aegaeum 20. Tsipopoulou M. 2002. Petras, Siteia: The Palace, the Town, the Hinterland and the Protopalatial Background. In J. Driessen, I. Schoep, R. Laffineur (eds.), Monuments of Minos. Rethinking the Minoan Palaces, Liege. Tzedakis, Y. & Chryssoulaki, S. 1987. Neopalatial Architectural Elements in the Area of Chania. In The Function of Minoan Palaces. Proceedings of the Fourth International Symposium at the Swedish Institute in Athens. 10-16 June 1984, Stockholm, 111-115. Tzedakis, Y. & Chryssoulaki, A., Voutsaki, S., Venieri, Y., 1989. Les Routes Minoennes: Rapport Preliminaire – Defense de la Circulation ou Circulation de la Defense. Bulletin de Correspondence hellenique 113, 43-75. Watrous, L.V. Review of Aegean Prehistory III: Crete from Earliest Prehistory through the Protopalatial Period. In T. Cullen (ed.), Aegean Prehistory: A Review, Boston, 157-223. Watrous, L.V., Hadzi-Villianou, D., Blitzer, H. 2004. The Plain of Phaistos: Cycles of Social Complexity in the Mesara Region of Crete, Monumenta Archaeologica 23, 272-290. Welwei, K.W. 2002. Die Grieschische Fruhzeit, Munchen. Whittaker, H. 2005. Social and Symbolic Aspects of Minoan writing. European Journal of Archaeology 8(2), 157-181. Wilson, 2008. Early Prepalatial Crete, The Cambridge Companion to the Aegean Bronze Age, Cambridge, 77-79. Younger J.G., Rehak P. 2008. Minoan Culture: Religion, Burial Customs, and Administration. In C.W. Shelmerdine (ed.), The Cambridge Companion to the Aegean Bronze Age, Cambridge, 173-185. Znamierowski, C. 2001. Elita i demokracja. In Elita, ustrój, demokracja, Warszawa.